A CHECKLIST OF THE FLORA OF SHANJAN PROTECTED AREA, EAST AZERBAIJAN PROVINCE, NW IRAN - Bibalani, Ghassem Habibi; Taheri, Elnaz (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The flora of protected Shanjan rangeland in Shabestar district, Azerbaijan Province, NW Iran was studied using a 1 m x 1 m quadrate in spring and summer 2011. The climate of this area is cold and dry. In this area 94 plant species belonging to 25 families were identified as constituting the major part of the vegetation. The families in the area are Amaryllidaceae, Amaryllidaceae, Boraginaceae, Campanulaceae, Caryophllaceae, Cistaceae, Compositea, Cruciferae, Cyperaceae, Dipesaceae, Euphorbiaceae, Geraniaceae, Hypericaceae, Linaceae, Melvaceae, Orobachaceae, Papaveraceae, Paronychiaceae, Plantaginaceae, Polygolaceae, Ranunculaceae, Resedaceae, Rubiaceae, Scrophulariaceae, ¬ Solanaceae and¬ Valerianacea. Floristic composition is Irano-Turanian elements. Detailed analysis showed that Biennial plants were 3.19%, Annual 41.49% and Perennial 55.32%.